Celso and Cora [videorecording] a Manila story - Kildea, Gary. ([Manila] s.n., 1983)
A Feature-length film which follows the daily lives of Celso and Cora, their two young children as they struggle against all odds to take out a life in a squatter community in the Philippine capital, Manila. Under the new deposed Marcos regime, their days are filled with desperation and hardship.
DVD
Directed by Gary Kildea.
Keywords: Documentary films; Feature films